Hemopoietic stem cells: stochastic differentiation and humoral control of proliferation. - Ogawa, M (1989)
The central feature of hemopoiesis is life-long, stable cell renewal. This process is supported by hemopoietic stem cells which, in the steady state, appear to be dormant in cell cycling. The entry into cell cycle of the dormant stem cells may be promoted by such factors as interleukin-1, interleukin-6 (IL-6), and granulocyte colony-stimulating factor (G-CSF). Once the stem cells leave G0 and begin proliferation, the subsequent process is characterized by continued proliferation and differentiation. While several models of stem cell differentiation have been proposed, micromanipulation studies of individual progenitors suggest that the commitment of multipotential progenitors to single lineages is a random (stochastic) process. The proliferation of early hemopoietic progenitors requires the presence of interleukin-3 (IL-3), and the intermediate process appears to be supported by granulocyte/macrophage colony-stimulating factor (GM-CSF). Once the progenitors are committed to individual lineages, the subsequent maturation process appears to be supported by late-acting, lineage-specific factors such as erythropoietin and G-CSF. Synthesis of a hemopoietic factor may take place in different cell types and is regulated by multiple factors. The physiological regulator of erythropoiesis is erythropoietin, which, by a feedback mechanism, provides fine control of erythrocyte production. Feedback mechanisms for leukocyte production have not been identified. It is possible that there is no feedback regulator of leukopoiesis. In this model, leukocyte production in the steady state is maintained at a genetically determined level. When an infection occurs, the bacterial lipopolysaccharides may augment the production of interleukin 1 alpha and beta, tumor necrosis factor, macrophage colony-stimulating factor, etc.(ABSTRACT TRUNCATED AT 250 WORDS)